Comparison of different electrode materials for the nitrate electrocatalytic reduction in a dual-chamber cell. Issue 5 (October 2020) - Beltrame, Thiago Favarini; Carvalho, Diogo; Marder, Luciano; Ulla, Maria Alicia; Marchesini, Fernanda Albana; Bernardes, Andrea Moura
Abstract: Nitrogen compounds in water are mainly associated to the use of fertilizers and to the discharge of industrial wastewater from tanneries, food and textile industry. The presence of high nitrate concentration in water can be dangerous to human health and the nitrate reduction through the electrocatalytic process is a promising treatment technology to minimize the presence of this ion in water resources. In this work, different sponge electrodes (Ni, Ni-Cu, Ni-Pd, Ni-Cu-Pd and Ni-Pd-Cu) were tested for the treatment of solutions containing high nitrate concentrations (600 mg L −1 of nitrate, that corresponds to 135.5 N-mg L -1 ). The electrodes are comprised of nickel (Ni) sponges that are chemically coated with copper (Cu) and/or palladium (Pd). A dual-chamber cell (DCC), separated by a cation-exchange membrane, was used for the nitrate reduction experiments. The obtained results indicated that it is possible to treat the nitrate solution by using nickel sponges coated with Pd and Cu as electrodes. The highest nitrate reduction (44 %) was obtained with a Ni-Cu electrode, being nitrite the main product generated. With the Ni-Pd-Cu electrode the highest ammonium formation (28 N-mg L -1 ) was obtained. The pH adjustment to 6−6, 5 increased the gaseous compounds formation (33 N-mg L -1 ). The results show that the process studied here can be used either as a first step treatment, to reduce nitrate to other chemical compounds, or as a final treatment, producing ammonium or nitrogen, when solutions of high nitrate concentration are being treated.